Interest In a becoming a Teacher Among sudents PKK Culinary Concentration After Educational Field Practice - Shahida, Siti Nur; Syarif, Wirnelis; Elida, Elida; Andriani, Cici (Universitas Negeri Padang, 2024)
This research aims to analyze students' interest in becoming teachers after carrying out educational field practice (PLK). To analyze PLK activities for PKK students with a Culinary Concentration Class of 2019. To analyze the influence of PLK on interest in becoming a teacher among PLL students with a Culinary Concentration Class of 2019. In this research, measurements will be taken to determine the interest of 2019 PKK Culinary Concentration students to become teachers after implementing PLK. This research is a type of ex post facto research using a quantitative approach. The population is students from the 2019 PKK Culinary Concentration Study Program using data analysis techniques, descriptive analysis tests, normality tests, linearity tests and hypothesis tests.The research results obtained are 1) PLK activities for students of the 2019 Culinary Concentration PKK Study Program in this research can be categorized as high, namely with a percentage of 74.9%. 2) Interest in becoming a teacher among students from the 2019 PKK Culinary Concentration Study Program in this research can be categorized as low, namely with a percentage of 79.1%. 3) In the linear hypothesis test, there is an influence of PLK activities (X) on interest in becoming a teacher (Y) among students of the 2019 Culinary Concentration PKK Study Program, which is indicated by a correlation coefficient of 0.039 with a coefficient of determination (R2) of X on Y of 0.102. This shows that the PLK activity variable has an influence on the interest in becoming a teacher among students of the 2019 Class of PKK Culinary Concentration Study Program by 12.1%.